The curriculum of Islamic studies and Islamic studies education programmes in meeting the challenges of globalization: a case studies of selected Malaysian universities - Hashim, Rosnani (IIUM Press, 2017)
Islamic studies or religious instruction is a subject that is taught throughout primary and secondary schooling, a period of about twelve years to Muslim students in Malaysia. This testifies its importance for the preservation of the Islamic tradition and as a precursor of change within the Muslim mind and soul. Islamic studies when properly taught, provides a great opportunity to transform Muslims’ lives especially in the era of globalization that is filled with challenges including the spread of Islamophobia. This article argues that this transformation is only possible if the curriculum of Islamic studies and Islamic studies education programs, which produce the teachers of Islamic studies, are sound and take into account the contemporary situation. Two important elements that are crucial in meeting the challenge of globalization and are consistent with the aims of higher Islamic studies are intellectualism and relevance of the Programs. Hence, this article examines the curriculum of higher Islamic Studies program in three universities and that of an Islamic Study teacher preparation program in Malaysia for their adequacy in generating Islamic intellectualism and relevance in the context of globalization. The article found that the Islamic Studies Programs at the universities are still traditional, although some changes have been made in order to stay relevant. But the programs still lack the ingredient of intellectualism due to its pedagogical approach. The article proposes some changes in the curriculum for its improvement.